2016
DOI: 10.4103/1735-5362.192488
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Melissa officinalis extract against H2O2-induced oxidative stress in human vascular endothelial cells

Abstract: Melissa officinalis L. is a medicinal plant with a large variety of pharmacological effects and traditional applications. This study aimed to evaluate the protective and antioxidant activities of the extract of M. officinalis aerial parts on human umbilical vein endothelial cells (HUVECs) under oxidative stress induced by H2O2. Cells were incubated with H2O2 (0.5 mM, 2 h) after pretreatment with M. officinalis extract (25-500 μg/mL). Cell viability was evaluated by 3-(4, 5- Dimethylthiazol-2-yl)-2, 5-diphenylt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 26 publications
(32 reference statements)
2
31
1
Order By: Relevance
“…Studies have shown that it exerts immunomodulatory and antioxidant effects by inducing the T-cell activation, suppressing the levels of interleukins including IL-6, TNF-α, and downregulating the ferritin (98). Also it suppresses H 2 O 2 -induced oxidative stress in human umbilical vein endothelial cells (99). Furthermore, zinc saturated Lf exerts a more potent antiviral effect (100).…”
Section: Lactoferrinmentioning
confidence: 99%
“…Studies have shown that it exerts immunomodulatory and antioxidant effects by inducing the T-cell activation, suppressing the levels of interleukins including IL-6, TNF-α, and downregulating the ferritin (98). Also it suppresses H 2 O 2 -induced oxidative stress in human umbilical vein endothelial cells (99). Furthermore, zinc saturated Lf exerts a more potent antiviral effect (100).…”
Section: Lactoferrinmentioning
confidence: 99%
“…Daily treatment with lactoferrin after unilateral hind limb surgeryinduced ischemia in C57BL/6J mice promoted angiogenesis, activated endothelial function via an NO-dependent mechanism 171 and protected HUVECs against hydrogen peroxide-induced oxidative stress. 172…”
Section: Breastfeedingmentioning
confidence: 99%
“…The mixtures were exposed at room temperature (25°C) for different time (0, 2, 4, and 6 h), and then incubated with HUVEC for 1 h (mixture:medium = 1:10, v/v). Then, HUVEC was treated with 3 mM H 2 O 2 for 1 h to induce oxidative stress ( Safaeian et al, 2016 ). Vitamin C (2.30, 0.76, 0.25, 0.08, 0.028, 0.0093, and 0.0031 mM) were used as positive controls.…”
Section: Methodsmentioning
confidence: 99%